Squatters and affordable houses in urban areas: law and policy in Malaysia - Sufian, Azlinor; Mohamad, Nor Asiah (Research Centre in Public Administration and Public Services (CCASP), Academy of Economic Studies, Bucharest, Romania, 2009)
Being one of the developing countries in Asia, squatters and housing are among the main subject of government focus in each development programmme in Malaysia. This article focuses on the issue of squatters and housing and seeks to present on how the Malaysian government has work towards providing a quality life and affordable housing to its citizens. Nonetheless, undoubtedly Malaysia is facing a crisis of urban squatters which has become a challenge for the local authorities as well as the federal government. Discussion on this topic will relate to the application of relevant laws and regulations that affect the responsibilities of local authorities, planning authorities and other related government agencies.